Composite plasticizer for high and low temperature resistant cable and preparation method thereof

A composite plasticizer for cables, combining modified citric acid polymer and chloroprene rubber with epoxy soybean oil, addresses temperature and UV resistance issues and environmental concerns by forming a stable network structure and neutralizing hydrogen chloride, thereby improving cable material performance.

CN119119747AActive Publication Date: 2024-12-13JIANGSU SENHE CHEM TECH CO LTD

Patent Information

Application Number
CN202411435620.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-13
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

Existing plasticizers for cables face challenges in high and low temperature resistance, UV resistance, and environmental impact, particularly with terephthalate esters and cyclohexane-1,4-diester esters exhibiting low temperature stability and volatility.

Method used

A composite plasticizer is formulated with a main plasticizer composed of modified citric acid polymer and chloroprene rubber, and an auxiliary plasticizer derived from epoxy soybean oil, using a combination of ether bonds and functional cross-linking agents to enhance thermal and UV stability, along with a filler and solvent system.

Benefits of technology

The composite plasticizer improves wear resistance, high and low temperature resistance, and UV resistance of cable materials by forming a complex spatial network structure and incorporating anti-ultraviolet groups, while also enhancing environmental friendliness by neutralizing hydrogen chloride gas during PVC processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005084867140000021
    Figure BDA0005084867140000021
  • Figure BDA0005084867140000031
    Figure BDA0005084867140000031
  • Figure BDA0005084867140000041
    Figure BDA0005084867140000041
Patent Text Reader

Abstract

The invention discloses a composite plasticizer for a high and low temperature resistant cable and a preparation method of the composite plasticizer, belongs to the technical field of plasticizers for cables, and aims to solve the technical problem that the high and low temperature resistance and the ultraviolet resistance of a composite plasticizer for a cable in the prior art need to be further improved. The preparation method comprises the following steps: uniformly mixing 30-50 parts by weight of a main plasticizer, 20-40 parts by weight of an auxiliary plasticizer, 20-40 parts by weight of an auxiliary material and 60-70 parts by weight of a solvent to obtain a composite plasticizer, preparing a citric acid copolymer and modified chloroprene rubber, and crosslinking the citric acid copolymer and the modified chloroprene rubber to obtain the main plasticizer; an auxiliary plasticizer is prepared through reaction of epoxidized soybean oil and a functional cross-linking agent, and the auxiliary plasticizer is further mixed with an auxiliary material and a solvent to obtain the composite plasticizer capable of enhancing wear resistance, high and low temperature resistance, ultraviolet resistance and toughness of the cable material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of processing plasticizers for cables, and in particular to a composite plasticizer for high and low temperature resistant cables and a preparation method thereof. Background Art

[0002] The use of plasticizers can be traced back to the late 19th century and early 20th century. The earliest plasticizers were natural resins and vegetable oils, which were used to improve the plasticity of rubber and plastics. With the development of the chemical industry, synthetic plasticizers began to be widely used after the 1930s. Early plasticizers were mostly phthalates and epoxy ester compounds, which were used to improve the softness and processing properties of PVC. In general, plasticizers, as an important chemical, play a key role in modern industry. Continuous technological innovation and application research will help improve their efficiency and environmental friendliness.

[0003] The prior art (CN108699287A) discloses a plasticizer composition, in which terephthalate esters and cyclohexane 1,4-diester esters are mixed. Although the terephthalate esters and cyclohexane 1,4-diester esters are optimized during the preparation process, it is still difficult to ensure the enrichment of terephthalate ester plasticizers in the organism and the impact on the ecological chain. The temperature resistance of cyclohexane-1,4-diester plasticizers is relatively low. Cyclohexane-1,4-diester plasticizers have high volatility and cannot maintain stability at high temperatures. Research has also found the following technical problems: the environmental protection of the main plasticizer terephthalate ester ester in the plasticizer composition needs to be improved, and the high temperature resistance, chemical stability and mechanical properties of the auxiliary catalyst cyclohexane 1,4-diester ester ester need to be improved.

[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0005] The object of the present invention is to provide a composite plasticizer for high and low temperature resistant cables and a preparation method thereof, so as to solve the technical problem that the high and low temperature resistance and UV resistance of the composite plasticizer for cables in the prior art need to be further improved.

[0006] The object of the present invention can be achieved by the following technical scheme: A composite plasticizer for high and low temperature resistant cables, comprising 30-50 parts by weight of a main plasticizer, 20-40 parts by weight of an auxiliary plasticizer, 20-40 parts by weight of an auxiliary material, and 60-70 parts by weight of a solvent;

[0007] The preparation method of the main plasticizer comprises the following steps: adding modified citric acid polymer, modified chloroprene rubber, dimethyl sulfoxide and 0.1-0.5 mol / L aluminum chloride solution into a reaction kettle, raising the temperature of the reaction kettle to 40-60 DEG C, keeping the temperature for reaction for 2-4 hours, and post-treating to obtain the main plasticizer.

[0008] The main plasticizer synthesis reaction equation is:

[0009]

[0010] The principle of the synthesis reaction of the main plasticizer is as follows: under the catalysis of Lewis acid aluminum chloride, the chlorine group of the modified chloroprene rubber generates an intermediate R-Cl-AlCl3 with stronger electron affinity. The generated chloride intermediate undergoes a nucleophilic substitution reaction with the hydroxyl group (-OH) in the modified citric acid polymer. The oxygen anion in the hydroxyl group attacks the methylene carbon in the intermediate to form a transition state. After nucleophilic substitution, a main plasticizer connected by an ether bond is prepared.

[0011] Furthermore, the dosage ratio of the modified citric acid polymer, the modified chloroprene rubber, the dimethyl sulfoxide and the 0.1-0.5 mol / L aluminum chloride solution is 5-8 g: 2-3 g: 15-20 mL: 5-10 mL, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction solution is added into a rotary evaporator with a water bath temperature of 80-100° C., and the main plasticizer is obtained by distillation under reduced pressure until no liquid is extracted.

[0012] Furthermore, the auxiliary materials include the following components in parts by weight: 0.1-1 parts of stabilizer, 5-15 parts of solvent, 1-5 parts of plasticizer activity regulator and 5-20 parts of filler; the stabilizer is one or more of diester zinc stabilizer, calcium zinc heat stabilizer HX-10 and lead-free calcium zinc stabilizer LX-800, the plasticizer activity regulator is one or more of diisooctyl phthalate, di(2-ethylhexyl) dibenzoate, dibutyl stearate and di(2-ethylhexyl) benzoate, the filler is one or more of sodium carboxymethyl cellulose, hydroxypropyl methylcellulose and glyceryl stearate; the solvent is a mixed solvent of ethanol and xylene in a mass ratio of 1-2:1.

[0013] Furthermore, the preparation method of the modified citric acid polymer is: citric acid, 1,4-butanediol, dimethyl sulfoxide and 70-98wt% sulfuric acid solution are added to a reactor, the temperature of the reactor is increased to 40-60°C, the reaction is kept warm for 2-4h, and the modified citric acid polymer is obtained by post-treatment.

[0014] The synthetic reaction equation of modified citric acid polymer is:

[0015]

[0016] The principle of the synthetic reaction of modified citric acid polymer is as follows: acidic conditions provide protons for the esterification reaction, prompting the hydrogen ions on the hydroxyl groups of 1,4-butanediol to leave and form a good leaving group, which enhances the electrophilicity of the hydroxyl group and makes it easy to attack the carbonyl carbon on the carboxyl carbon atom of citric acid, so that citric acid and 1,4-butanediol phenol are connected by an ester bond, and then the remaining hydroxyl groups at the end undergo an esterification reaction with the remaining citric acid molecules again to form a long-chain polymer.

[0017] Furthermore, the dosage ratio of citric acid, 1,4-butanediol, dimethyl sulfoxide and 70-98wt% sulfuric acid solution is 8-10g:3-4g:10-15mL:5-10mL, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and distilled under reduced pressure until no liquid is extracted to obtain a modified citric acid polymer.

[0018] Furthermore, the preparation method of the modified chloroprene rubber is as follows: chloroprene rubber with a molecular weight of 1000-1200, 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol, xylene and 0.1-0.5 mol / L aluminum chloride solution are added into a reactor in a dosage ratio of 8-10 g:3-5 g:30-40 mL:5-10 mL, the temperature of the reactor is increased to 40-60° C., the reaction is kept warm for 2-4 hours, and the modified chloroprene rubber is obtained by post-treatment.

[0019] The synthetic reaction equation of modified chloroprene rubber is:

[0020]

[0021] The principle of the modified chloroprene rubber synthesis reaction is as follows: under the catalysis of Lewis acid aluminum chloride, the chlorine group of the chloroprene rubber generates an intermediate R-Cl-AlCl3 with stronger electron affinity. The generated chloride intermediate undergoes a nucleophilic substitution reaction with the hydroxyl group (-OH) in 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol, and the oxygen anion in the hydroxyl group attacks the methylene carbon in the intermediate to form a transition state. After nucleophilic substitution, a modified chloroprene rubber connected by an ether bond is prepared.

[0022] Furthermore, the post-treatment includes: after the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80-100° C., and the reaction liquid is distilled under reduced pressure until no liquid is extracted to obtain the modified chloroprene rubber.

[0023] Furthermore, the preparation method of the auxiliary plasticizer is: adding a functional crosslinking agent, epoxy soybean oil, triethylamine and N,N-dimethylformamide into a reactor, raising the temperature of the reactor to 60-80°C, keeping the reaction temperature for 1-3 hours, and post-treating to obtain the auxiliary plasticizer.

[0024] The auxiliary plasticizer synthesis reaction equation is:

[0025]

[0026] The principle of the auxiliary plasticizer synthesis reaction is: under weak alkaline conditions, the hydroxyl (-OH) of the functional cross-linking agent and the epoxy group in the epoxy soybean oil undergo a ring-opening reaction, and the functional cross-linking agent and the epoxy soybean oil are polymerized through ether bonds to modify the benzene ring and phosphate group inside the epoxy soybean oil to prepare the auxiliary plasticizer.

[0027] Furthermore, the dosage ratio of the functional crosslinking agent, epoxy soybean oil, triethylamine and N,N-dimethylformamide is 3-5g:10-12g:1-2g:40-50mL, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is extracted to obtain an auxiliary plasticizer.

[0028] Furthermore, the preparation method of the functional cross-linking agent is: add 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, triethylamine and N,N-dimethylformamide into a reactor in a dosage ratio of 8-10g:3-5g:0.5-1g:30-40mL, increase the temperature of the reactor to 60-80°C, keep the reaction warm for 1-3h, and post-treat to obtain the functional cross-linking agent.

[0029] The synthetic reaction equation of the functional cross-linking agent is:

[0030]

[0031] The principle of the synthesis reaction of the functional cross-linking agent is: under weak alkaline conditions, the hydroxyl group (-OH) of binaphthol phosphate and the epoxy group of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane undergo a ring-opening reaction, and binaphthol phosphate and 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane are polymerized through ether bonds to prepare a functional cross-linking agent.

[0032] Furthermore, the post-treatment includes: after the reactor is cooled to room temperature, the reaction solution is added into a rotary evaporator with a water bath temperature of 80-100° C., and the reaction solution is distilled under reduced pressure until no liquid is extracted to obtain a functional cross-linking agent.

[0033] Furthermore, the preparation method of the composite plasticizer for high and low temperature resistant cables is as follows: the main plasticizer, the auxiliary plasticizer, the auxiliary material and the solvent are added into a reaction kettle and mixed evenly, and the mixture is passed through a 100-mesh sieve to obtain the composite plasticizer.

[0034] Furthermore, the preparation method of the cable material is: adding polyvinyl chloride, composite plasticizer and auxiliary materials into a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed port toward the discharge port are 160°C, 165, 165°C, 170°C, 170°C, 180°C, and 180°C respectively, the main engine speed of the twin-screw extruder is 80-120rpm, and the pressure is 100-150bar to obtain the cable material by melt extrusion.

[0035] The present invention has the following beneficial effects:

[0036] 1. In the process of preparing a composite plasticizer for a high and low temperature resistant cable, the present invention prepares a main plasticizer and an auxiliary plasticizer, and mixes them with a filler to obtain a composite plasticizer; in the process of preparing the main plasticizer, citric acid is used as a base material, 1,4-butanediol is used as a cross-linking agent to prepare a modified citric acid polymer, and 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol is used to crosslink a small molecular weight chloroprene rubber. The modified material is modified, and finally the chloroprene rubber is grafted onto the modified citric acid polymer to prepare the main plasticizer; in the process of preparing the auxiliary catalyst, naphthol phosphate is reacted with 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane to prepare a functional cross-linking agent, which is further grafted onto the base material epoxy soybean oil to prepare the auxiliary plasticizer; through the synergistic combination of the main plasticizer, the auxiliary plasticizer and the auxiliary materials, a composite plasticizer is obtained which can enhance the wear resistance, high and low temperature resistance, UV resistance and toughness of the cable material.

[0037] 2. In the process of preparing a composite plasticizer for high and low temperature resistant cables, the present invention uses citric acid as the base material of the main plasticizer, and uses 1,4-butanediol as a modified citric acid copolymer formed by a cross-linking agent to form a complex spatial network structure. The complex spatial network structure can not only give the main plasticizer excellent mechanical properties, but also cooperate with the large number of ester bonds formed to make the main plasticizer have extremely strong thermal stability; a modified chloroprene rubber with a small molecular weight is selected and modified by 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol to prepare the modified chloroprene rubber, and the small molecular weight chloroprene rubber can be cross-linked with 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol. The anti-ultraviolet groups cooperate with each other to make the main catalyst have extremely high anti-ultraviolet performance; after organic reaction, the modified chloroprene rubber and the modified citric acid copolymer are connected by ether bonds to prepare the main plasticizer, in which the complex spatial network structure cooperates with the modified chloroprene rubber to make the main plasticizer have extremely strong wear resistance and toughness; the modified chloroprene rubber and a large number of ester bonds in the spatial network structure cooperate with each other to jointly improve the heat resistance of the main plasticizer, making it have extremely strong thermal stability; the anti-ultraviolet groups in the modified chloroprene rubber and 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol cooperate with each other to greatly improve the anti-ultraviolet performance of the main plasticizer, and finally a composite plasticizer main material that enables the cable material to have excellent wear resistance, heat resistance and UV resistance is prepared.

[0038] 3. In the process of preparing a composite plasticizer for high and low temperature resistant cables, the present invention uses epoxy soybean oil as a base material of an auxiliary plasticizer, uses binaphthol phosphate and 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane to prepare a functional crosslinking agent, and binaphthol phosphate and 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane are connected by a ring-opening reaction, wherein the silicon-oxygen bond of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane cooperates with the phosphoric acid group and benzene ring in binaphthol phosphate to make the auxiliary plasticizer have extremely strong low temperature resistance, and the silicon-oxygen bond also enhances the crosslinking ability of organic materials and inorganic materials in the preparation process of cable materials, and indirectly improves the wear resistance of the plasticizer; Then, the functional cross-linking agent is connected to the epoxy soybean oil through a one-step ring-opening reaction. The rich epoxy structure on the epoxy soybean oil cooperates with the silicon-oxygen bond, benzene ring and phosphate group on the functional cross-linking agent to jointly improve the low-temperature resistance of the auxiliary plasticizer. Among them, the rich benzene ring structure on the auxiliary plasticizer also cooperates with the complex spatial network structure in the main plasticizer to improve the wear resistance of the composite plasticizer. In the process of preparing cable materials using commonly used PVC resins, the rich epoxy groups in the auxiliary plasticizer absorb the hydrogen sulfide gas generated during the processing of polyvinyl chloride, making the cable preparation process more environmentally friendly. Through the above methods, a composite plasticizer auxiliary material that enables cable materials to have excellent wear resistance and low-temperature resistance is finally prepared. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The density of polyethylene used in the present invention is 0.91-0.92 g / cm 3 , crystallinity is 48-52%, and molecular weight is 25000-50000.

[0041] Example 1

[0042] This embodiment provides a method for preparing a composite plasticizer for high and low temperature resistant cables, comprising the following steps:

[0043] S1. Preparation of primary plasticizer

[0044] 79.4 g of citric acid, 39.4 g of 1,4-butanediol, 99.3 mL of dimethyl sulfoxide and 99.3 mL of 75 wt% sulfuric acid solution were weighed and added to a reactor. The temperature of the reactor was raised to 40° C. and the reaction was kept warm for 2 hours. After the reactor was cooled to room temperature, the reaction liquid was added to a rotary evaporator with a water bath temperature of 60° C. and distilled under reduced pressure until no liquid was produced, to obtain 117.3 g of a modified citric acid polymer;

[0045] 63.2 g of chloroprene rubber with a molecular weight of 1059.3, 39.5 g of 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol, 276.5 mL of xylene and 79.0 mL of 0.1 mol / L aluminum chloride solution were weighed and added to a reactor. The temperature of the reactor was raised to 40° C. and the reaction was kept warm for 2 hours. After the reactor was cooled to room temperature, the reaction solution was added to a rotary evaporator with a water bath temperature of 80° C. and distilled under reduced pressure until no liquid was produced to obtain 98.3 modified chloroprene rubber;

[0046] 100.0 g of modified citric acid polymer, 60.0 g of modified chloroprene rubber, 300.0 mL of dimethyl sulfoxide and 100.0 mL of 0.1 mol / L aluminum chloride solution were weighed and added into a reactor. The temperature of the reactor was raised to 40°C and the reaction was kept warm for 4 hours. After the reactor was cooled to room temperature, the reaction solution was added into a rotary evaporator with a water bath temperature of 80°C and distilled under reduced pressure until no liquid was extracted to obtain 156.3 g of the main plasticizer.

[0047] S2. Preparation of auxiliary plasticizer

[0048] 40.0 g of binaphthol phosphate, 12.0 g of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, 2.0 g of triethylamine and 120.0 mL of N,N-dimethylformamide were weighed and added to a reactor. The temperature of the reactor was raised to 60° C. and the reaction was kept warm for 1 hour. After the reactor was cooled to room temperature, the reaction solution was added to a rotary evaporator with a water bath temperature of 80° C. and distilled under reduced pressure until no liquid was produced, to obtain 48.3 g of a functional cross-linking agent;

[0049] 36.0 g of functional cross-linking agent, 72.0 g of epoxy soybean oil, 7.2 g of triethylamine and 360.0 mL of N,N-dimethylformamide were weighed and added into a reactor. The temperature of the reactor was raised to 60°C and kept warm for 1 hour. After the reactor was cooled to room temperature, the reaction liquid was added into a rotary evaporator with a water bath temperature of 80°C and distilled under reduced pressure until no liquid was extracted to obtain 103.7 g of auxiliary plasticizer.

[0050] S3. Preparation of composite plasticizer

[0051] Weigh 1.9 g of calcium zinc heat stabilizer HX-10, 12.4 g of dibutyl stearate, and 49.7 g of glyceryl stearate to prepare 64.0 g of auxiliary material;

[0052] 100.0 g of the main plasticizer, 100.0 g of the auxiliary plasticizer, 64.0 g of the auxiliary material, 100.0 g of ethanol and 100.0 g of xylene were weighed and added into a reactor, mixed evenly, and passed through a 100-mesh sieve to obtain 462.5 g of a composite plasticizer.

[0053] S4. Preparation of cable materials

[0054] 1500.0g of polyvinyl chloride, 450.0g of composite plasticizer and 225.0g of auxiliary materials were weighed and added to a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed port to the discharge port were 160°C, 165, 165°C, 170°C, 170°C, 180°C, and 180°C, respectively. The main engine speed of the twin-screw extruder was 80rpm and the pressure was 100bar. The cable material was obtained by melt extrusion.

[0055] Example 2

[0056] This embodiment provides a method for preparing a composite plasticizer for high and low temperature resistant cables, comprising the following steps:

[0057] S1. Preparation of primary plasticizer

[0058] 82.1 g of citric acid, 32.8 g of 1,4-butanediol, 123.2 mL of dimethyl sulfoxide and 82.1 mL of 85 wt% sulfuric acid solution were weighed and added to a reactor. The temperature of the reactor was raised to 40° C. and the reaction was kept warm for 2 h. After the reactor was cooled to room temperature, the reaction solution was added to a rotary evaporator with a water bath temperature of 100° C. and distilled under reduced pressure until no liquid was produced, to obtain 110.5 g of a modified citric acid polymer;

[0059] Weigh 63.1 g of chloroprene rubber with a molecular weight of 1123.2, 25.2 g of 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol, 214.4 mL of xylene and 50.5 mL of 0.5 mol / L aluminum chloride solution into a reactor, raise the temperature of the reactor to 60°C, keep the reaction temperature for 4 hours, cool the reactor to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain 84.5 g of modified chloroprene rubber;

[0060] 120.0 g of modified citric acid polymer, 45.0 g of modified chloroprene rubber, 300.0 mL of dimethyl sulfoxide and 120 mL of 0.5 mol / L aluminum chloride solution were weighed and added into a reactor. The temperature of the reactor was raised to 60°C and kept warm for 4 hours. After the reactor was cooled to room temperature, the reaction solution was added into a rotary evaporator with a water bath temperature of 100°C and distilled under reduced pressure until no liquid was extracted to obtain 158.3 g of the main plasticizer.

[0061] S2. Preparation of auxiliary plasticizer

[0062] 60.0 g of binaphthol phosphate, 24.0 g of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, 4.85 g of triethylamine and 210.0 mL of N,N-dimethylformamide were weighed and added to a reactor. The temperature of the reactor was raised to 80° C. and the reaction was kept warm for 3 hours. After the reactor was cooled to room temperature, the reaction solution was added to a rotary evaporator with a water bath temperature of 100° C. and distilled under reduced pressure until no liquid was extracted to obtain 82.3 g of a functional cross-linking agent.

[0063] 36.0 g of functional cross-linking agent, 72.0 g of epoxy soybean oil, 12.0 g of triethylamine and 288.0 mL of N,N-dimethylformamide were added to the reactor, the temperature of the reactor was raised to 80°C, and the reaction was kept warm for 3 hours. After the reactor was cooled to room temperature, the reaction liquid was added to a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid was extracted, to obtain 103.5 g of auxiliary plasticizer.

[0064] S3. Preparation of composite plasticizer

[0065] Weigh 4.1 g of calcium zinc heat stabilizer HX-10, 15.3 g of dibutyl stearate and 61.2 g of glyceryl stearate to obtain 80.6 g of auxiliary material;

[0066] 108.0 g of the main plasticizer, 90.0 g of the auxiliary plasticizer, 72.0 g of the auxiliary material, 128.0 g of ethanol and 64.0 g of xylene were weighed and added into a reactor, mixed evenly, and passed through a 100-mesh sieve to obtain 458.5 g of a composite plasticizer.

[0067] S4. Preparation of cable materials

[0068] 1500.0g of polyvinyl chloride, 450.0g of composite plasticizer and 225.0g of auxiliary materials were weighed and added to a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed port to the discharge port were 160°C, 165, 165°C, 170°C, 170°C, 180°C, and 180°C, respectively. The main engine speed of the twin-screw extruder was 120rpm and the pressure was 150bar, and the cable material was obtained by melt extrusion.

[0069] Example 3

[0070] This embodiment provides a method for preparing a composite plasticizer for high and low temperature resistant cables, comprising the following steps:

[0071] S1. Preparation of primary plasticizer

[0072] 79.3 g of citric acid, 26.4 g of 1,4-butanediol, 105.7 mL of dimethyl sulfoxide and 98 wt % sulfuric acid solution were weighed and added to a reactor. The temperature of the reactor was raised to 50° C. and the reaction was kept warm for 3 hours. After the reactor was cooled to room temperature, the reaction solution was added to a rotary evaporator with a water bath temperature of 90° C. and distilled under reduced pressure until no liquid was produced, to obtain 102.6 g of a modified citric acid polymer;

[0073] Weigh 61.2 g of chloroprene rubber with a molecular weight of 1032.5, 27.2 g of 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol, 258.4 mL of acetone and 54.4 mL of 0.3 mol / L aluminum chloride solution into a reactor, raise the temperature of the reactor to 50°C, and keep the reaction for 3 hours. After the reactor is cooled to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 90°C, and distill under reduced pressure until no liquid is produced to obtain 84.6 g of modified chloroprene rubber;

[0074] 100.0 g of modified citric acid polymer, 50 g of modified chloroprene rubber, 300.0 mL of dimethyl sulfoxide and 150.0 mL of 0.3 mol / L aluminum chloride solution were weighed and added into a reactor. The temperature of the reactor was raised to 50°C and kept warm for 3 hours. After the reactor was cooled to room temperature, the reaction solution was added into a rotary evaporator with a water bath temperature of 90°C and distilled under reduced pressure until no liquid was extracted to obtain 143.6 g of the main plasticizer.

[0075] S2. Preparation of auxiliary plasticizer

[0076] 64.0 g of binaphthol phosphate, 32.0 g of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, 6.4 g of triethylamine and 288.0 mL of N,N-dimethylformamide were weighed and added to a reactor. The temperature of the reactor was raised to 70° C. and the reaction was kept warm for 2 h. After the reactor was cooled to room temperature, the reaction solution was added to a rotary evaporator with a water bath temperature of 90° C. and distilled under reduced pressure until no liquid was produced, to obtain 92.5 g of a functional cross-linking agent;

[0077] 40.0 g of functional cross-linking agent, 100.0 g of epoxy soybean oil, 18.0 g of triethylamine and 420.0 mL of N,N-dimethylformamide were added to the reactor, the temperature of the reactor was raised to 70°C, and the reaction was kept warm for 2 hours. After the reactor was cooled to room temperature, the reaction liquid was added to a rotary evaporator with a water bath temperature of 90°C, and distilled under reduced pressure until no liquid was extracted, to obtain 128.5 g of auxiliary plasticizer.

[0078] S3. Preparation of composite plasticizer

[0079] Weigh 2.6 g of calcium zinc heat stabilizer HX-10, 17.2 g of dibutyl stearate, and 64.5 g of glyceryl stearate to prepare 84.3 g of auxiliary material;

[0080] 120.0 g of the main plasticizer, 90.0 g of the auxiliary plasticizer, 80.0 g of the auxiliary material, 130.0 g of the ethanol solvent and 65.0 g of xylene were weighed and added into a reactor, mixed evenly, and passed through a 100-mesh sieve to obtain 483.5 g of a composite plasticizer.

[0081] S4. Preparation of cable materials

[0082] 1500.0g of polyvinyl chloride, 450.0g of composite plasticizer and 225.0g of auxiliary materials were weighed and added to a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed port to the discharge port were 160°C, 165, 165°C, 170°C, 170°C, 180°C, and 180°C, respectively. The main engine speed of the twin-screw extruder was 100rpm and the pressure was 125bar to obtain the cable material by melt extrusion.

[0083] Comparative Example 1

[0084] The difference between this comparative example and Example 3 is that in step S1, an equal amount of acetyl tributyl citrate is used to replace the modified citric acid polymer.

[0085] Comparative Example 2

[0086] The difference between this comparative example and Example 3 is that in step S3, an equal amount of acetyl tributyl citrate is used to replace the main plasticizer.

[0087] Comparative Example 3

[0088] The difference between this comparative example and Example 3 is that in step S3, an equal amount of epoxy soybean oil is used to replace the auxiliary plasticizer.

[0089] Comparative Example 4

[0090] The difference between this comparative example and Example 3 is that step S2 is eliminated and an equal amount of triester phosphate is used to replace the auxiliary plasticizer.

[0091] Performance Testing:

[0092] The acid gas content released during the preparation of cable materials using the composite plasticizer in Examples 1-3 and Comparative Examples 1-4 was measured by referring to the standard GB / T 2917.1-2002 "Determination of hydrogen chloride and any other acidic products released from blends and products based on vinyl chloride homopolymers and copolymers at high temperatures - Congo red method" to determine the release of acidic gas during the preparation of cable materials; the wear resistance, toughness and high and low temperature resistance of the cable materials prepared using the composite plasticizer in Examples 1-3 and Comparative Examples 1-4 were tested. The wear resistance was tested with reference to GB / T17737.324-2018 "Coaxial communication cable Part 1-324: Mechanical test method Cable wear resistance test" for the wear resistance of the cable material; the toughness was tested with reference to GB / T 17737.316-2018 "Coaxial communication cable Part 1-316: Mechanical test method Cable maximum tensile test" for the maximum tensile strength of the cable material; the high temperature resistance was tested with reference to the standard GB / T GB / T 2951.42-2008 "General test methods for insulation and sheathing materials of electric and optical cables Part 42: Special test methods for polyethylene and polypropylene mixtures Test for tensile strength and elongation at break after high temperature treatment Winding test after high temperature treatment Winding test after air heat aging to determine the increase in mass Long-term thermal stability test Copper catalytic oxidation degradation test method to determine the cable's" Determine the softness of cable materials after high temperature treatment and the cracking of cables treated at 100°C for 42 days; GB / T 2951.14-2008 "General test methods for insulation and sheathing materials of electric and optical cables Part 14: General test methods for low temperature test" Determine the softness of cable materials after high temperature treatment and the cracking of cables treated at 100°C for 42 days; GB / T 2951.14-2008 "General test methods for insulation and sheathing materials of electric and optical cables Part 14: General test methods for low temperature test" Determine the softness of cable materials after 40°C below zero The softness of the cable material after low-temperature treatment at ℃ for 16 hours and the cracking after the drop hammer impact; the anti-ultraviolet polyolefin cable materials of Examples 1-3 and Comparative Examples 1-4 were subjected to an ultraviolet aging test. The test conditions were irradiation with a 5kW xenon lamp and water spraying at a water pressure of 0.20MPa, and periodic ultraviolet irradiation was performed according to a cycle of 120 minutes, of which 20 minutes were sprayed with water and irradiated at the same time, and the remaining 100 minutes were illuminated alone, for a total of 1000 cycles. After that, the sample was left to stand at room temperature for 24 hours, and the wear resistance, toughness and high and low temperature resistance of the cable material were tested again. The specific test data are shown in Tables 1-3:

[0093] Table 1 - Release of acidic gases during sample preparation

[0094]

[0095] Table 2-Performance test data of samples

[0096]

[0097]

[0098] Table 3-Performance test data of samples after ultraviolet cyclic radiation

[0099]

[0100] Data Analysis:

[0101] Comparative analysis of the data in Table 1-2 shows that in the process of preparing cable materials using the composite plasticizer prepared in this experiment, the abundant epoxy groups and other active functional groups inside the cable materials can effectively neutralize the hydrogen chloride gas released by polyvinyl chloride during the preparation process, thereby protecting the environment. The cable materials prepared by using the composite plasticizer prepared in this experiment can resist blade scraping for 143 times, can be wound for 8 times after high temperature treatment, and do not crack after being treated at 100°C for 42 days. After being treated at -40°C for 16 hours, the cable materials can be wound for 9 times and do not crack after a drop hammer impact test. The tensile strength reaches 223MPa.

[0102] By comparing the data of Example 3, Comparative Example 1 and Comparative Example 2, it can be found that the main plasticizer prepared in this experiment improves the high temperature resistance, toughness and wear resistance of the cable material through its excellent spatial structure, a large number of high temperature resistant functional groups and modified chloroprene rubber;

[0103] By comparing the data of Example 3, Comparative Example 3 and Comparative Example 4, it can be found that the auxiliary plasticizer prepared in this experiment significantly improves the low temperature resistance, toughness and wear resistance of the cable through a large number of low temperature resistant functional groups, epoxy groups and siloxy groups inside it;

[0104] In summary, the composite plasticizer prepared through this experiment has a significant effect on improving the wear resistance, toughness and high and low temperature resistance of cable materials.

[0105] The data in Table 3 are analyzed. After 1000 times of ultraviolet radiation, the cable material prepared by using the composite plasticizer prepared in this experiment can resist blade scraping for 125 times. After high temperature treatment, the cable material can be wound for 7 times. After 42 days of heat preservation at 100°C, the cable material does not crack. After 16 hours of low temperature treatment at -40°C, the cable material can be wound for 8 times and does not crack after the drop hammer impact test. The tensile strength reaches 223MPa.

[0106] From the data in the comparison table, it can be found that compared with Examples 1-3, Comparative Example 3 and Comparative Example 4, the performance of Comparative Example 1 and Comparative Example 2 is significantly reduced after ultraviolet cyclic radiation, indicating that the complex spatial structure and anti-ultraviolet groups in the prepared main plasticizer cooperate with each other to make the cable material prepared by using the composite plasticizer prepared in this experiment have excellent ultraviolet resistance.

[0107] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0108] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0109] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A composite plasticizer for high and low temperature resistant cables, It is characterized in that The composition comprises 30-50 parts by weight of a main plasticizer, 20-40 parts by weight of an auxiliary plasticizer, 20-40 parts by weight of an auxiliary material and 60-70 parts by weight of a solvent; The preparation method of the main plasticizer is as follows: adding modified citric acid polymer, modified chloroprene rubber, dimethyl sulfoxide and 0.1-0.5 mol / L aluminum chloride solution into a reactor, raising the temperature of the reactor to 40-60°C, keeping the temperature for reaction for 2-4 hours, and post-treating to obtain the main plasticizer.

2. A composite plasticizer for high and low temperature resistant cables according to claim 1, It is characterized in that The auxiliary materials include the following components in parts by weight: 0.1-1 parts of stabilizer, 1-5 parts of plasticizer activity regulator and 5-20 parts of filler; the stabilizer is one or more of diester zinc stabilizer, calcium zinc heat stabilizer HX-10 and lead-free calcium zinc stabilizer LX-800, the plasticizer activity regulator is one or more of diisooctyl phthalate, di(2-ethylhexyl) dibenzoate, dibutyl stearate and di(2-ethylhexyl) benzoate, the filler is one or more of sodium carboxymethyl cellulose, hydroxypropyl methylcellulose and glyceryl stearate; the solvent is a mixed solvent of ethanol and xylene in a mass ratio of 1-2:

1.

3. A composite plasticizer for high and low temperature resistant cables according to claim 2, It is characterized in that The dosage ratio of the modified citric acid polymer, the modified chloroprene rubber, the dimethyl sulfoxide and the 0.1-0.5 mol / L aluminum chloride solution is 5-8 g: 2-3 g: 15-20 mL: 5-10 mL. The post-treatment comprises: after the reaction kettle is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80-100 DEG C, and the main plasticizer is obtained by distillation under reduced pressure until no liquid is extracted.

4. The composite plasticizer for high and low temperature resistant cables according to claim 1, It is characterized in that The preparation method of the modified citric acid polymer is as follows: citric acid, 1,4-butanediol, dimethyl sulfoxide and 70-98wt% sulfuric acid solution are added into a reactor, the temperature of the reactor is increased to 40-60°C, the reaction is carried out by heat preservation for 2-4h, and the modified citric acid polymer is obtained by post-treatment.

5. The composite plasticizer for high and low temperature resistant cables according to claim 4, It is characterized in that The dosage ratio of citric acid, 1,4-butanediol, dimethyl sulfoxide and 30-50wt% sulfuric acid solution is 8-10g:3-4g:10-15mL:5-10mL. The post-treatment includes: after the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain a modified citric acid polymer.

6. The composite plasticizer for high and low temperature resistant cables according to claim 1, It is characterized in that The preparation method of the modified chloroprene rubber is as follows: chloroprene rubber with a molecular weight of 1000-1200, 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol, xylene and 0.1-0.5 mol / L aluminum chloride solution are added into a reaction kettle in a dosage ratio of 8-10 g:3-5 g:30-40 mL:5-10 mL, the temperature of the reaction kettle is increased to 40-60° C., the reaction is kept warm for 2-4 hours, and the modified chloroprene rubber is obtained by post-treatment.

7. The composite plasticizer for high and low temperature resistant cables according to claim 1, It is characterized in that The preparation method of the auxiliary plasticizer is as follows: functional crosslinking agent, epoxy soybean oil, triethylamine and N,N-dimethylformamide are added into a reactor, the temperature of the reactor is increased to 60-80°C, the reactor is kept warm for 1-3 hours, and the auxiliary plasticizer is obtained by post-processing.

8. The composite plasticizer for high and low temperature resistant cables according to claim 7, It is characterized in that The dosage ratio of the functional crosslinking agent, epoxy soybean oil, triethylamine and N,N-dimethylformamide is 3-5g:10-12g:1-2g:40-50mL. The post-treatment includes: after the reaction kettle is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is extracted to obtain an auxiliary plasticizer.

9. The composite plasticizer for high and low temperature resistant cables according to claim 8, It is characterized in that The preparation method of the functional cross-linking agent is as follows: adding binaphthol phosphate, 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, triethylamine and N,N-dimethylformamide into a reaction kettle at a dosage ratio of 8-10g:3-5g:0.5-1g:30-40mL, raising the temperature of the reaction kettle to 80-100°C, keeping the temperature for reaction for 1-3h, and post-treating to obtain the functional cross-linking agent.

10. A method for preparing the composite plasticizer for high and low temperature resistant cables according to any one of claims 1 to 9, It is characterized in that The preparation method of the composite plasticizer for high and low temperature resistant cables comprises: adding a main plasticizer, an auxiliary plasticizer, auxiliary materials and a solvent into a reaction kettle, mixing them evenly, and passing them through a 100-mesh sieve to obtain the composite plasticizer.

Citation Information

Patent Citations

  • Electric wire and cable soft polychloroethylene plastics for vehicle and preparation method thereof

    CN101386697A

  • Chloroprene rubber and graphene composite material and preparation method thereof

    CN106117681A

  • High-temperature-resistant flame-retardant PVC cable material and preparation method thereof

    CN110218402A

  • High-temperature-resistant tough PVC cable material and preparation method thereof

    CN113652039A

  • Trimellitic bio-based plasticizer

    CN114805928A

Cited By

  • Low-atomization low-odor plasticizer and preparation method thereof

    CN121293770A